Effects of Some Common Food Constituents on Cardiovascular Disease. (16th June 2011) - Yang, Yaling; Chan, Sze Wa; Hu, Miao; Walden, Richard; Tomlinson, Brian
Abstract : Cardiovascular diseases are the major cause of morbidity and mortality worldwide, and there is considerable interest in the role of dietary constituents and supplements in the prevention and treatment of these disorders. We reviewed the major publications related to potential effects on cardiovascular risk factors and outcomes of some common dietary constituents: carotenoids, flavonoid-rich cocoa, tea, red wine and grapes, coffee, omega-3 fatty acids, and garlic. Increased intake of some of these has been associated with reduced all-cause mortality or reduced incidence of myocardial infraction, stroke, and hypertension. However, although the evidence from observational studies is supportive of beneficial effects for most of these foodstuffs taken as part of the diet, potential benefits from the use of supplements derived from these natural products remain largely inconclusive.